1999
DOI: 10.1093/carcin/20.9.1809
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of the tobacco-specific carcinogen 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK) in freshly isolated human lung cells

Abstract: Metabolism of the tobacco-specific nitrosamine 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK) was characterized in human lung cells isolated from peripheral lung specimens obtained from 12 subjects during clinically indicated lobectomy. NNK biotransformation was assessed in preparations of isolated unseparated cells (cell digest), as well as in preparations enriched in alveolar type II cells, and alveolar macrophages. Metabolite formation was expressed as a percentage of the total recovered radioactivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
28
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 33 publications
4
28
0
Order By: Relevance
“…By the same token, the rates of NNK ␣-hydroxylation were, on average, only ϳ40% higher in microsomes containing 3 to 20 fmol/mg CYP2A13 than in microsomes containing Ͻ2 fmol/mg CYP2A13; the rate difference would be much greater if the rates were normalized by total protein in airway epithelial cells, rather than by proteins of all lung cells. In support of this idea, a previous study had reported increased formation of NNK ␣-hydroxylation products in an enriched human alveolar type II cell preparation, compared with the amounts formed by a mixed population of lung cells or an enriched alveolar macrophage preparation (Smith et al, 1999). Even in individuals with Ͻ2 fmol CYP2A13/mg microsomal protein, CYP2A13 may still play an important role in NNK metabolic activation in airway epithelial cells, a notion supported by the 30% reduction in activity rendered by the addition of 8-MOP to CYP2A13-Low samples.…”
mentioning
confidence: 79%
“…By the same token, the rates of NNK ␣-hydroxylation were, on average, only ϳ40% higher in microsomes containing 3 to 20 fmol/mg CYP2A13 than in microsomes containing Ͻ2 fmol/mg CYP2A13; the rate difference would be much greater if the rates were normalized by total protein in airway epithelial cells, rather than by proteins of all lung cells. In support of this idea, a previous study had reported increased formation of NNK ␣-hydroxylation products in an enriched human alveolar type II cell preparation, compared with the amounts formed by a mixed population of lung cells or an enriched alveolar macrophage preparation (Smith et al, 1999). Even in individuals with Ͻ2 fmol CYP2A13/mg microsomal protein, CYP2A13 may still play an important role in NNK metabolic activation in airway epithelial cells, a notion supported by the 30% reduction in activity rendered by the addition of 8-MOP to CYP2A13-Low samples.…”
mentioning
confidence: 79%
“…Before use, the purity of H]NNK was assessed, since high purity (Ͼ98%) was needed to ensure that impurities would not interfere with quantification of metabolites. If purity was Ͻ98%, H]NNK was purified by high-performance liquid chromatography as described previously (Smith et al, 1999). Incubation mixtures were prepared as described previously (Smith et al, 2003), using 4.2 M [5-3 H]NNK and 1.0 mg of microsomal protein in a total volume of 1.0 ml.…”
Section: Methodsmentioning
confidence: 99%
“…These endpoint metabolites are used in assessing the degree of NNK bioactivation, since their formation is indicative of the formation of the DNA-reactive metabolites. The detoxification of NNK and NNAL occurs mainly through pyridine N-oxidation, which results in the formation of excretable N-oxides (Hecht, 1998).Cytochromes P450 (P450s), specifically CYP2A6/2A13, CYP2B6, CYP3A4/3A5, and CYP2E1 (Smith et al, 1992(Smith et al, , 1995(Smith et al, , 1999(Smith et al, , 2003Hecht, 1998), and prostaglandin H synthase (Smith et al, 1995(Smith et al, , 1999 but not lipoxygenases (Bedard et al, 2002) have been implicated in human pulmonary NNK metabolism. Of particular interest are the CYP2A isozymes CYP2A13 and CYP2A6.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cytochrome P450 may also biotransform the tobacco specific carcinogens to 4-(methylnitrosamine)-1-(-3-pyridine)-1-butadone (NNK). If so, both alveolar type II cells and macrophages may be target cells for NNK toxicity [39].…”
Section: Pneumoproteinaemia In Smokersmentioning
confidence: 99%